Matematyka

Autorzy:Drążek Anna, Duvnjak Ewa, Kokiernak-Jurkiewicz Ewa

Wydawnictwo:WSiP

Rok wydania:2016

Po wyłączeniu wspólnego czynnika przed nawias wyrażenie 4.2 gwiazdek na podstawie 5 opinii
  1. Gimnazjum
  2. 2 Klasa
  3. Matematyka

Po wyłączeniu wspólnego czynnika przed nawias wyrażenie

7
 Zadanie
8
 Zadanie
9
 Zadanie
10
 Zadanie

11
 Zadanie

12
 Zadanie
12
 Zadanie

`(x^2-6x)*2x-2x^2(6-x)=x(x-6)*2x-2x^2(6-x)=-2x^2(6-x)-2x^2(6-x)=(-2x^2-2x^2)(6-x)=(-4x^2)(6-x)=`

`=4x^2(x-6)=4x(x^2-6x)=-4x(-x^2+6x)`

Odpowiedź:

A, B, D